Studies of the Dimensionless Mass-transfer Coefficient During the Adsorption of Basic and Acid Dyes on to Bagasse Pith - Mamdouh M. Nassar; Mohammed S. El-Geundi (Adsorption Science & Technology, 1994)
The influence of agitation, particle diameter and mass of adsorbent on the external mass-transfer coefficient is discussed. The computed values correlate with the dimensionless function Sh/Sc 1/3 . It has been found that Sh/Sc 1/3 varies linearly with the variables studied and may be correlated with system variables via the equation Sh/Sc 1/3 = A(variable) B .